The right to development and its corresponding obligations on developing countries - Masum, Ahmad (Universiti Utara Malaysia Press, 2013)
The right to development is a fundamental right, the precondition of liberty, progress, justice and creativity. This right has raised many expectations and controversies over the years. Developing countries claim that the international economic and political order constitutes an obstacle to the enjoyment of the right to development for their citizens. They therefore see a need for action in the international dimension of the right to development.In their view, they are able to provide the necessary basis for the enjoyment of the right to development only if the international order becomes more conducive to the economic development of developing countries.This paper aims to examine the concept of the right to development as a ‘human right’ focusing mainly on the position of developing countries as to whether they have an obligation to work towards the realization and implementation of this right. The paper concludes that the right to development is now recognized as a ‘human right’ like other internationally accepted human rights.Thus, being a right, it entails obligations of some agents in the society, who have the power to deliver the right or adopt policies that have a high likelihood of delivering the right.